Memory (translation. a transdisciplinary journal, 2022)
Translation is an intercultural as well as a translingual phenomenon, a transcultural as well as an interlingual process. It involves the transfer of a narrative or text from one signifying form to another, the transporting of texts from one historical context to another, and the tracking of the migration of meanings from one cultural space to another.